Implementación de simulaciones para el aprendizaje de fundamentos matemáticos de las funciones reales con una variable real - Erazo Escudero, Ayrton Daniel (2023)
ABSTRACT This investigation occurred in the Educational Unit "Athens" of Ambato, with the students of the Second Year of the Unified General Baccalaureate. The students of this institution need help understanding functions due to the need for knowledge of the mathematical foundations of processes. For this reason, the research focuses on designing simulations in which the undamentals of natural functions with a real variable are shown. It was sought to determine if there was an improvement in students' academic performance with the use of simulations compared to students who did not use them. Therefore, the research carried out was quasi-experimental. The development of the simulations was given in the free software octave; for the collection of data, an objective test was taken, the same one developed and approved in previous investigations. For the analysis of the data obtained from the accurate test, a descriptive analysis of each question was carried out based on the mathematical foundation analyzed. Several normality tests were developed to apply the t-student statistic, checking if the academic performance of the group with which the simulations were used obtained a better average than the group that did not use them. Consequently, the research concludes that the use of simulations positively influences students' academic performance since it allows them to observe the fundamentals of functions, which tend to be abstract on many occasions. Keywords: functions, fundamental, performance, academic, simulations.